Ecology of Love and Avoidance Negotiating the Boundaries Between World-Affirmation and World-Renunciation - Saucier, Melanie (Université d'Ottawa | University of Ottawa, 2009)
This study examines the intersection between religion and environmental ethics in South Asian traditions, namely that of Jainism. Religious traditions, as they confront the challenges of modernity, are redefining their traditional mores and narratives in ways that are contemporary and relevant. One of the most striking ways Jains are accomplishing this is by interpreting the self as inherently “ecological”, and applying “Western” animal rights discourse to traditional Jain doctrine. This study will explore how such new understandings are being established by members of these “living” communities, and argue for the reevaluation of such reified concepts as “ecology” and “religion.”